Stephen J. Ball, Meg Maguire, Annette Braun. "How schools do policy. Policy enactments in secondary schools" - Rujas Martínez-Novillo, Javier (Revista Española de Investigaciones Sociológicas, 2024)
How schools do policy: policy enactments in secondary schools Stephen J. Ball, Meg Maguire, Annette Braun Routledge, 2012